Profiles of Grammatical Morphology and Sentence Imitation in Children With Specific Language Impairment and Down Syndrome. - Eadie, P. A.; Fey, M. E.; Douglas, J. M. (Journal of Speech, Language & Hearing Research, 2002)
The purpose of the present study was to examine the grammatical morphology and sentence imitation performance of two different groups of children with language impairment and to compare their performance with that of children learning language typically. Expressive use of tense-bearing and non-tense-related grammatical morphemes was explored. Children with specific language impairment (SLI), with Down syndrome (DS), and with typical language development (TL) were matched on mean length of utterance (MLU). Performance was compared primarily on composite measures of tense, tense inflections, and non-tense morphemes, as well as on the Sentences subtest of the Wechsler Preschool and Primary Scale of Intelligence—Revised (WPPSI-R; D. Wechsler, 1989). Exploratory analyses were completed on a set of 11 individual grammatical morphemes as a follow-up to the principal analyses. As predicted, the children with SLI performed significantly more poorly than the children with TL on all three composite measures. In addition, the DS group exhibited significantly weaker performance than did the TL group on the tense inflections and non-tense morpheme composites. Although there were no statistically reliable differences between the SLI and DS groups on any morpheme measure, the groups were not comparably weak in their use of the regular past, -ed; the irregular third person singular morphemes (e.g., has, does); the present progressive, -ing; or the use of modals. The SLI and DS groups both performed more poorly than did the TL group on the sentence imitation task. Reprinted by permission of the publisher.